The vocational qualification system in Korea - (:unkn) unknown (My University, 1999)
This publication provides an overview of the development of vocational qualification systems in Korea. The information is presented in three sections: I. National technical qualification system; II. National qualification system of non-technical categories; III. Private vocational qualification system. The first section provides an overview of the Korean qualification system, discusses the developments in the history of the national technical qualification system, its enactment and structure, the administration of the certification process, the formulation and administration of exams, and the credit bank system which recognises training and experiences accumulated by an individual outside the school environment. The second section provides an overview of the non-technical categories of the national qualification system, gives examples of various government ministries' operation of non-technical fields, and discusses the credit bank system in relation to the non-technical categories. The final section provides an overview of the private qualification system and its current status and discusses the operations of five private qualification providers. (BIBB-Doku)
Keywords: S 1 Stufen der Berufsbildung; I 2.3.4 Asien; Berufsbildung; Technische Bildung; Qualifikation; Zertifizierung; Korea